Invasive Streptococcus pyogenes Infections in <3-Month-Old Infants in France: Clinical and Laboratory Features - Zoé Germont; Philippe Bidet; Philippe Bidet; Céline Plainvert; Céline Plainvert; Céline Plainvert; Stéphane Bonacorsi; Stéphane Bonacorsi; Claire Poyart; Claire Poyart; Claire Poyart; Claire Poyart; et al. (Frontiers Media S.A., 2020)
Few data are available on invasive group A Streptococcus (GAS) infections (IGASIs) in infants. We described initial clinical and laboratory features and outcomes of <3-month-old infants hospitalized for an IGASI between 2007 and 2016 in France. Patients were identified from the French National Reference Centre for streptococci. IGASI was defined by the isolation of GAS from blood cultures or from other usually sterile sites. Data collection was performed by assessing the patients' hospitalization reports. Twenty-six patients (15 males; 57.7%) were included. Among 19 cases with available data, 14 (73.7%) were household contacts of a GAS infection, reaching 8/9 (88.9%) in neonates. The diagnoses were bacteremia (n = 18; 69.2%), pleural effusion or pneumonia (n = 6; 23.1%), meningitis with brain abscess (n = 1; 3.8%), and septic arthritis (n = 1; 3.8%). Fever (n = 10; 38.5%), hemodynamic disorders (n = 11; 42.3%), respiratory disorders (n = 7; 26.9%), thrombocytopenia (n = 7; 26.9%), and neutropenia (n = 5; 19.2%) were frequently observed. The main emm-genotype was emm-1 (n = 8; 30.8%). Thirteen (50.0%) infants have been admitted to the intensive care unit, and two (7.7%) died. Respiratory disorders, high C-reactive protein level, and the need for transfusion were significantly associated with severity. IGASI remains uncommon in <3-month-old children but leads to a high morbidity. Whether an antibiotic prophylaxis for contact neonates of a patient with GAS infection decreases the risk of infection remains to be determined.